E-INVOICING IMPLEMENTATION: ADOPTION CHALLENGES AMONG SMEs AND IMPLICATIONS FOR STAKEHOLDERS - Suzana San; Nik Zam Nik Wan; Syuhaila Razak; Noraida Saidi; Masdiah Abdul Hamid (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Electronic invoicing, commonly referred to as e-invoicing, represents a crucial component of the ongoing digital transformation within the realm of taxation. The gradual implementation of e-invoicing in Malaysia began in 2024. The shift to e-invoicing signifies considerable advancements in tax digitalization, aimed at improving transparency and ensuring tax compliance, especially for small and medium enterprises (SMEs), which are the backbone of the national economy. An e-invoice serves as a digital representation of a transaction between a supplier and a buyer, effectively substituting conventional paper or any other electronic format. Although e-invoicing offers numerous advantages, SMEs have encountered challenges that could impede the transition to tax digitalization. Consequently, this conceptual paper aims to present a comprehensive overview of the adoption of e-invoicing by identifying the challenges encountered by SMEs and the impacts of the new system on the stakeholders. This research aims to assist tax authorities in achieving a seamless transition to e-invoicing by identifying the potential challenges that may hinder its adoption and examining how digital tax reforms affect different stakeholders. This study contributes to the ongoing discussion surrounding digital taxation by offering recommendations for the successful implementation and preparedness of e-invoicing within SMEs in Malaysia.